Evaluasi Kecukupan Tebal Lead Apron Guna Mendukung Jaminan Keselamatan Radiasi pada Unit Pelayanan Radiologi Rumah Sakit - Yeti Kartikasari; Darmini Darmini; Dwi Rochmayanti (Jurnal LINK, 2015)
This study aims to determine adequacy of thick protective lead aprons as radiation in Radiology Services Unit in Semarang. This research is quantitative with observational approach radiation measurements. The samples were hospitals in Kota Semarang. The independent variable is the thickness of the lead apron and the dependent variable in this study is the radiation behind the lead apron. Data analysis was performed using descriptive statistics to take a conclusion. The results showed Adequacy lead apron at the Semarang Hospital, HVL values between 4 to 7 HVL or dose rate are forwarded after passing through the apron of 6.25% to 0, 781%. Value adequacy thick lead apron 0.5 mmPb that used had a value below the threshold set by Bapeten that dose forwarded after passing the lead apron is less than or 0,02 μSv which means lead apron can be used for radiation safety assurance in hospital and radiology departement units in the Semarang.